Cladocera fauna composition in a river-lagoon system of the upper Paraná River floodplain, with a new record for Brazil - Serafim Jr. M.; Lansac-Tôha F. A.; Paggi J. C.; Velho L. F. M.; Robertson B. (Brazilian Journal of Biology, 2003)
Cladocera communities were studied in lotic and lentic environments of the Upper Paraná River floodplain, State of Mato Grosso do Sul, Brazil. A total of 63 species of Cladocera were identified in 108 samples. Of these, 24 species are considered new records for that floodplain, and one is a new record for Brazil. Chydoridae was the most representative family with 19 genera and 39 species.